FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI WISATAWAN MANCANEGARA BERKUNJUNG KE PURA PUSEH DESA ADAT BATUAN, GIANYAR - Kadek Sandra Putri Dewanti; I Made Sendra; I GPB. Sasrawan Mananda (Jurnal IPTA (Industri Perjalanan Wisata), 2018)
The purpose of this research is to know the potential of Puseh and Desa Temple at Batuan Village as a tourist destination and the factors that influence the motivations of foreign tourists visiting those temple. This research was using quantitative descriptive supported by SPSS Version 17.0. The result showed that Puseh and Desa Temple at Batuan Village have a cultural potency to be a tourist destination for foreign tourist visiting those temple. The tourists are dominated by female, the age of tourists are dominated by 25-44 years old and the nationality of foreign tourists are dominated by Australian. According to the validity and reliability test of 18 variables showed that all of the variables are valid and reliable. Accordingly, the variables could be proceeded to the factor analyze. According to the factor analyze test, there are three factors that influence the motivations of foreign tourists visiting Puseh and Desa Temple at Batuan Village, such as 1) The pull factors involved culture uniqueness, historical heritage, arts, custom, new experiences, comfortable, seeing the local peoples preparing the small offerings, easy to access and physiological satisfaction. 2) The promotion factors involved influence of family, influence of co-workers, information from travel agent and information from internet. 3) Push factors involved prestige, temple structure, social interaction, influence of friends and escape as well.